(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This article presents some considerations on the uses of the concept of human dignity in bioethics and biolaw. Starting from the observation of the intrinsic vagueness of the notion, the first section of the article aims at showing that in bioethics the vagueness can be managed by linking the concept of dignity to the concept of individual autonomy. The second section, taking into consideration the Directive 98/44 on the legal protection of biotechnological inventions, stresses the difficulties of the use of the principle of the respect for human dignity as a source of legal regulations.